Is capnometry helpful in children with bronchiolitis?. (April 2016) - Jacob, Ron; Bentur, Lea; Brik, Riva; Shavit, Itai; Hakim, Fahed
Abstract: Background: Acute bronchiolitis is the most frequent lower respiratory tract infection in infants. Only small subsets of patients develop severe disease resulting in hospitalization despite having no identifiable risk factors. There is still a debate as to the role of capnometry in assessing ventilation in children with acute respiratory distress, and bronchiolitis in particular. Methods: This was a prospective, single blind cohort study in which children younger than two years presenting to the emergency department (ED) with bronchiolitis were included. Our primary outcome was the correlation between the end tidal CO2 (EtCO2 ) and the clinical decision of hospital admission and discharge. Our secondary outcome measure was the correlation of EtCO2 upon arrival to the ED and clinical measures of bronchiolitis severity. Finally, by using multivariate models, we looked for other parameters that could contribute to the prediction of illness severity. Results: One hundred and fourteen children with bronchiolitis were evaluated. Their median EtCO2 upon arrival to the ED was 34 mmHg (range 24–65 mmHg). EtCO2 values upon admission or discharge were not statistically different among patients who were hospitalized and among those who were discharged from the ED. Among admitted patients, we found no correlation between capnometry readings at admission and number of oxygen desaturation days, nor with the length of hospitalization. Wang clinical respiratory severity score was found, by using multivariate models, to predict nasogastric tube need, oxygen desaturation days, and length of hospitalization. Conclusion: Capnometry readings upon arrival to the ED did not predict hospital admission or hospital discharge eligibility. Among hospitalized patients, EtCO2 did not correlate with the evaluated disease severity measures. Wang score was found to be the most consistent predictor of significant outcomes. Highlights: Capnometry did not predict hospital admission or hospital discharge eligibility. Among hospitalized patients, capnometry did not correlate with disease severity. Wang score was found to be the most consistent predictor of significant outcomes.